Elaboración de un software educativo para la enseñanza-aprendizaje del bloque numérico en matemática de los alumnos del tercer y cuarto grado de educación general básica de la escuela de educación básica “Francia” del cantón Quilanga, provincia de Loja, periodo 2013-2014. - Cueva Rojas, Lourdes Lisbeth (2015)
Teaching today means to motivate and engage students in a process of construction and reconstruction of their own knowledge, skills, attitudes, emotions, behavior, and values. For the importance of the use of technologies for developing skills in students in the area of mathematics, is that the present research work, called arises: “DEVELOPMENT OF AN EDUCATIONAL SOFTWARE FOR LEARNING IN BLOCK NUMBER OF MATH STUDENT OF THIRD AND FOURTH GRADE GENERAL EDUCATION BASIC EDUCATION SCHOOL BASIC "FRANCIA” Quilanga CANTON, Loja Province, 2013-2014 " The general objective that guided this research was: To develop educational software for teaching and learning math the number pad of the students of the third and fourth grades of basic education in the School of Basic Education "Francia" Quilanga Canton province Loja period 2013-2014 The methods used were: Scientist, Descriptive and Inductive-Deductive. The techniques applied were: Survey applied to Parents and teachers to know how is taking the learning process of children in third and fourth grade. App of the Survey of Parents and teachers found that: 100% of Parents and teachers agree that educational software is needed in the field of mathematics. Similarly; 84% of surveyed parents and 100% of teachers believe that the implementation of an educational software to improve the teaching-learning process. Finally the conclusions and recommendations that follow from the interpretation and analysis of the data and its comparison with the theoretical and conceptual references, which concludes that educational software should be used by students in 3rd and 4th year of basic education arise as it influences the development of their skills and also helps in better understanding of the subject of mathematics